Method for consolidating sandy soil by combining curdlan with MICP (Micro Inductively Coupled Plasma) technology
By combining MICP technology with canal glue, the problem of MICP technology has limited flexural effect in consolidating sand soil is solved, and the unbounded compressive strength and calcium carbonate formation of the sand column are significantly improved, forming a denser calcite aggregate. The mechanical properties of the sand column are enhanced and the problems of high price and toxicity of strengthening agents in the prior art are solved.
Patent Information
- Application Number
- CN202410145776.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2024-12-13
AI Technical Summary
The existing MICP technology has limited flexural resistance when consolidating sandy soil, which limits its widespread use in engineering applications. In addition, existing reinforcers such as silk fibroin are expensive and crosslinking agents are toxic, so simple and effective methods are needed. Improve consolidation strength.
Using the MICP technology, the cementitious solution is formed by mixing it well with Bacillus Pasteuris bacterial solution and calcium chloride solution. Through multiple rounds of grouting process, the calcium carbonate generation is promoted and the sand column is enhanced. mechanical properties.
The unbounded compressive strength of the sand column is significantly improved, the formation of calcium carbonate particles is increased, and the formation of denser calcite aggregates is formed, which enhances the mechanical properties of the sand column and reduces the permeability of the cementitious liquid.
Smart Images

Figure CN119121889A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soil ecological protection engineering, and in particular to a soil reinforcement implementation method for consolidating sandy soil by using a novel curdlan combined with MICP technology. Background Art
[0002] With the continuous development of urbanization and infrastructure construction, the demand for cement continues to grow, becoming an indispensable building material in modern construction and engineering. However, the production and use of cement will have a negative impact on the environment, including the high-temperature calcination in its production process will release a large amount of carbon dioxide, causing a greenhouse effect, exacerbating global warming, and inducing a series of ecological problems. In addition, the mining of raw materials and waste disposal will also pollute the land and destroy biodiversity. Therefore, it is crucial to find a new sustainable and environmentally friendly material and measures to replace cement.
[0003] In civil and construction engineering practice, biopolymers have been widely used in building materials such as concrete mixtures, drilling fluids and cement grouting, acting as plasticizers or viscosity enhancers. In the field of geotechnical engineering, there are examples of introducing biopolymers as new materials in the fields of soil treatment and foundation improvement. The calcium carbonate formed by MICP mineralization can cement loose particles into a whole, significantly improve the strength and anti-erosion properties of the sand body, improve the pore structure of the sand, and reduce the permeability. Initial results have been achieved in strengthening the sand. However, in the process of MICP application, it was found that the anti-flexural effect of sand consolidated by microbial mineralization by adding bacteria alone was general, which limited its wider engineering application.
[0004] Therefore, it is urgent to seek a simple and effective method to improve the consolidation strength. At present, there are some relevant reports on microbial consolidation of sandy soil. For example, the prior art with publication number CN115354644A discloses a method for reducing the number of MICP solidified soil pouring times, by adding flocculants and the like as reinforcing agents in the cementing liquid, not only can the loose soil be quickly solidified and formed, but also the number of pouring times can be greatly reduced, and it has a certain unconfined compressive strength, so it is convenient for construction and saves materials. The prior art with publication number CN115895666A discloses a method for MICP-modified silk fibroin synergistic solidification of sandy soil, by adding a silk fibroin solution modified by a cross-linking agent into the grouting liquid of the MICP technology, the MICP curing effect can be effectively improved, and the strength of the sandy soil after curing can be improved. However, the price of silk fibroin is relatively high, and the cross-linking agents such as glutaraldehyde used for modification have certain toxicity.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for consolidating sand by combining curdlan with MICP technology.
[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is: A method for consolidating sandy soil by using curdlan combined with MICP technology includes the following specific steps: Step 1: Weigh the sieved standard sand, mix it with the corresponding mass concentration of curdlan, and put it into a customized mold to make a sand column sample with a height of 70-90 mm; the weight of the standard sand is 130-150 g, and it is fine sand after passing through a 55-65 mesh sieve. The customized mold is a PVC cylinder with an open top and a sealed bottom. The inner diameter of the PVC cylinder is 35-38 mm and the height is 110-130 mm. A 200 μL pipette tip is inserted into the bottom as a sample addition channel, and two layers of medical gauze are placed at the bottom of the mold; Step 2: After adding the filtered sterilized urea solution to the sterilized culture medium, the bacteria are inoculated into the culture medium and cultured under shaking to obtain a Bacillus pasteurianus bacterial solution in the logarithmic growth phase; wherein the culture medium needs to be sterilized at high temperature and high pressure before adding the filtered sterilized urea solution, the culture medium is NB-Urea liquid culture medium, and the components of NB-Urea liquid culture medium include at least 8-12 g / L of peptone, 4-6 g / L of beef extract, 4-6 g / L of sodium chloride, and 8-12 g / L of ammonium sulfate; after the bacteria are inoculated into the culture medium, the culture is cultured under shaking for 12-15 hours, the culture temperature is 28-35°C, and the shaking speed is 170-190 rpm; Step 3: Mix equal volumes of calcium chloride solution and urea solution to prepare a cementing solution; wherein the concentration of the calcium chloride solution is 2 mol / L, the concentration of the urea solution is 2 mol / L, the concentration of the cementing solution is 1 mol / L, and the cementing solution is a volume mixture of the calcium chloride dihydrate solution and the urea solution; Step 4: Inject 1.1 times the pore volume of sterile water through the grouting port of the mold and place it in an incubator to saturate the sample; wherein, after the sterile water is injected into the customized mold, place it in a 30°C constant temperature incubator for 24 hours to saturate the sample, and the grouting rate of the peristaltic pump is 1 mL / min; Step 5: After saturation, inject the fixative solution and let it stand in an incubator; wherein, after injecting the fixative solution, let it stand in a 30°C constant temperature incubator for 6 hours, and the fixative solution is 0.05 mol / L calcium chloride dihydrate solution; Step 6: After the standing is completed, the cementing liquid is injected and the mixture is placed in an incubator; wherein, after the cementing liquid is injected, the mixture is placed in an incubator at a constant temperature of 30° C. for 6 hours; Step 7: centrifuge the bacterial solution in step 2, discard the supernatant and use fresh culture medium to make a bacterial solution resuspension with an OD of 1, inject it into the incubator and let it stand after step 6 is left to stand, wherein step 6 and step 7 constitute one round of grouting, and a total of fourteen rounds of grouting are performed, and react for 20 hours after the last round of injection of the cementing liquid and the bacterial solution resuspension; wherein, the Bacillus pasteurianus bacterial solution is centrifuged at 4°C and 6000r for 5 minutes, and the bacterial solution resuspension is left to stand in a 30°C constant temperature incubator for 20 hours after injection; Step 8: After the grouting is completed, the sand column is demolded, the sample is rinsed with deionized water, and it is placed in an oven and dried to constant weight for an unconfined compressive strength (UCS) test. The unconfined compressive strength (UCS) test is performed using a YYW-Ⅲ digital lime unconfined pressure gauge.
[0008] Among them, the liquid injection amount in step 4, step 5, step 6 and step 7 is 1.1 times the pore volume of the sand sample.
[0009] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time: The water holding capacity of the curdlan of the present invention can retain more cementing liquid and microorganisms, that is, retain more Ca 2+ , giving the opportunity to generate more calcium carbonate particles.
[0010] The UCS of the sand column added with 0.5% curdlan of the present invention reaches an average of 255KPa, which is 1.75 times that of the blank group. The dehydration shrinkage of curdlan can closely connect the sand particles. Curdlan also induces the formation of new calcite with a clustered morphology, promotes the formation of denser clustered flower-like aggregates of calcite, and enhances the mechanical properties of the sand column. In addition, the "bridge" formed by the intermolecular hydrogen bonds formed by the curdlan as an adhesive glue between the particles increases the friction and tension between the particles, and improves the mechanical properties of the sand column through effective energy dissipation.
[0011] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 This is a schematic diagram of the test grouting process in Example 1 of the present invention; Figure 2 This is a diagram of the amount of cementing fluid retained during the grouting process in Example 3 of the present invention; Figure 3 This is a graph of microbial adsorption rate during grouting in Example 4 of the present invention; Figure 4 This is a graph showing the amount of calcium carbonate generated at different locations of the sand column in Example 5 of the present invention; Figure 5 This is a graph showing the unconfined compressive capacity test results of a sand column in Example 5 of the present invention; Figure 6 is the XRD diagram of the sand column particles treated with curd rubber in Example 7 of the present invention; Figure 7 This is the FTIR image of the sand column particles treated with 0.5% mass concentration of curd in Example 7 of the present invention; Figure 8 This is a SEM image of sand column particles treated with 0.5% mass concentration of curd in Example 7 of the present invention; Fig. 9 This is the SEM image of the blank-treated sand column particles in Example 7 of the present invention.
[0013] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0014] The present invention will now be described in further detail with reference to the accompanying drawings.
[0015] Microbial induced calcium precipitation (MICP) is an environmentally friendly geological reinforcement technology that uses urease-producing bacteria in nature to decompose urea to produce carbonate ions, which combine with free metal cations in nature to form carbonate precipitation. The calcium carbonate formed by MICP can cement loose particles into a hard whole, thereby significantly improving the strength of the sand body, improving the pore structure of the sand, and reducing the permeability.
[0016] Curdlan is a polysaccharide with gelling properties, thermal stability and syneresis shrinkage. It is insoluble in water, alcohol and most organic solvents, but easily soluble in aqueous solutions of substances that have a destructive effect on hydrogen bonds, such as urea solutions. The purpose of the present invention is to overcome the above-mentioned shortcomings and provide a method for consolidating sandy soil by combining curdlan with MICP technology to solve the problems raised in the background technology. It comprises the following steps: Step 1: Weigh 140g of standard sand after passing through a 60-mesh sieve, mix it thoroughly with the corresponding mass concentration of curdlan, and put it into a customized mold to make a sand column sample with a height of 80mm; Step 2: Prepare the NB-Urea liquid culture medium required for Bacillus pasteurianus, add the filtered and sterilized urea solution after high temperature and high pressure sterilization, inoculate the bacteria into the NB-Urea liquid culture medium and shake culture for 14 hours to obtain the Bacillus pasteurianus bacterial solution in the logarithmic growth phase; Step 3: prepare 2 mol / L calcium chloride solution and 2 mol / L urea solution respectively, and mix the two solutions in equal volumes to prepare 1 mol / L cementing solution; Step 4: Use a peristaltic pump to inject 1.1 times the pore volume of sterile water through the injection port at the bottom of the mold and place it in a 30°C constant temperature incubator for 24 hours to saturate the sample; Step 5: After saturation, inject the fixative solution (0.05 M CaCl2·2H2O solution) and place in a 30℃ constant temperature incubator for 6 hours; Step 6: After standing, inject the cementing liquid and stand in a 30°C constant temperature incubator for 4 hours; Step 7: Centrifuge the bacterial solution in step 1 at 4°C and 6000r for 5 min, discard the supernatant and use fresh NB-Urea medium to make a bacterial solution resuspension with an OD of 1, inject it after step 6 is completed, and let it stand in a constant temperature incubator at 30°C for 20 hours; steps 6 and 7 are one round of grouting, and a total of 14 rounds of grouting are performed; Step 8: After grouting, demould the sand column, rinse the sample gently with deionized water, and bake it in a 55°C oven until constant weight; perform UCS test.
[0017] Furthermore, in step 1, the custom mold is a PVC cylinder with an open top and a sealed bottom, an inner diameter of 36.5 mm, and a height of 120 mm. A 200 μL pipette tip is inserted into the bottom as a sample addition channel, and two layers of medical gauze are placed on the bottom of the mold.
[0018] Furthermore, in step 2, the culture medium is NB-Urea liquid culture medium.
[0019] Furthermore, in step 2, the NB-Urea liquid culture medium contains at least 8-12 g / L of peptone, 4-6 g / L of beef extract, 4-6 g / L of sodium chloride, and 8-12 g / L of ammonium sulfate.
[0020] Furthermore, in step 2, the culture temperature of the system is 28-35° C., and the shaking speed is 180 rpm.
[0021] Furthermore, in step 3, the binder solution is a mixture of equal volumes of calcium chloride dihydrate solution and urea solution.
[0022] Furthermore, the grouting rate of the peristaltic pump in step 4 is 1 mL / min.
[0023] Furthermore, in step 5, the fixing liquid is 0.05 mol / L calcium chloride dihydrate solution.
[0024] Furthermore, the liquid injection amount in step 4, step 5, step 6 and step 7 is 1.1 times the pore volume of the sand sample.
[0025] Furthermore, the UCS test described in step 8 is performed using a YYW-III digital lime unconfined pressure instrument with a strain rate of 3 mm / min and a maximum range of 5 kN.
[0026] Compared with the prior art, the beneficial effects and advantages of the present invention are: The water holding capacity of curdlan can retain more cementing fluid and microorganisms, that is, more Ca 2+ , giving the opportunity to generate more calcium carbonate particles.
[0027] The UCS of the sand column with 0.5% curdlan added reached an average of 255KPa, which is 1.75 times that of the blank group. The dehydration shrinkage of curdlan can tightly connect the sand particles. Curdlan also induces the formation of new calcite with a clustered morphology, promotes the formation of denser clustered flower-like aggregates of calcite, and enhances the mechanical properties of the sand column. In addition, the curdlan acts as an adhesive glue between particles to form intermolecular hydrogen bonds to form a "bridge" that increases the friction and tension between particles, thereby improving the mechanical properties of the sand column through effective energy dissipation. In order to more clearly explain the purpose, technical solutions and beneficial effects of the present invention, the present invention is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0028] Example 1 Preparation of sand sample A PVC cylinder with an open top and sealed bottom was customized, with an inner diameter of 36.5 mm and a height of 120 mm. A round hole was melted in the center of the bottom with a heated iron needle, and then a 200 μL pipette tip was inserted as the sample addition channel. In order to prevent the sand sample from flowing out of the sample addition hole and blocking the sample addition hole, two layers of medical gauze were placed on the bottom of the mold to prevent sand particles from falling into the sample addition channel and blocking the entrance; 140 g of standard sand after passing through a 60-mesh sieve was weighed and fully mixed with the corresponding mass concentration of curdlan powder, and then loaded into the customized mold using a three-stage compaction method to make a sand column sample about 80 mm high.
[0029] Example 2 Preparation of bacterial solution Prepare 1L NB-Urea liquid culture medium, the formula is: 10g peptone, 5g beef extract, 5g sodium chloride, 10g ammonium sulfate, 950mL pure water, autoclave at 121℃ for 20min, weigh 20g urea and dissolve it in 50ml pure water to make urea solution, wait for the sterilized culture medium to cool naturally to about 80℃, add the prepared urea solution (the final concentration of urea is 20g / L) through a syringe filter in the clean bench to obtain 1L NB-Urea liquid culture medium. Inoculate the strain with an appropriate amount of NB-Urea liquid culture medium and shake and culture at 30℃ and 180rpm. Centrifuge the Bacillus pasteurianus culture liquid at 4℃ and 6000r for 5min after 14h of culture, discard the supernatant and add an appropriate amount of fresh NB-Urea culture medium, shake well to make a bacterial liquid resuspension with an OD of 1, and set aside.
[0030] The carbonate mineralizing bacteria used is Sporosarcina pasteurii, with strain number ATCC11859, which is a commercial model strain.
[0031] Example 3 Effect of adding curdlan during grouting on the amount of cement retained First, saturate the sample. Use a peristaltic pump to inject 1.1 times the pore volume of sterile water at a rate of 1 mL / min through the grouting port at the bottom of the mold. Then connect the grouting port to a hose with an inner diameter of 2 mm, clamp the hose with a water stop clamp, and place it in a constant temperature incubator at 30°C for 24 hours to saturate the sample. Figure 1 Schematic diagram of the grouting process.
[0032] After saturation, the fixative solution (0.05 M CaCl2·2H2O solution) was injected and the cells were placed in a 30°C constant temperature incubator for 6 h.
[0033] After standing, the cementing solution (a mixture of 1M CaCl2·2H2O and urea) was injected and the samples were placed in a 30°C constant temperature incubator for 4 h.
[0034] Then open the grouting port, collect the overflowing cementing liquid, weigh the volume of the collected liquid with a measuring cylinder, and subtract the overflow volume from the injected volume to roughly calculate the retained amount of cementing liquid. Figure 2The results show that in the early stage of grouting, the amount of cement retained gradually increased with the increase of the content of curdlan, and the increase of the content of curdlan was small. The retention of the cement was increased by about 10 mL with the increase of the content of curdlan. The retention rate of the cement was about 83% in the first grouting, which was 19% higher than that of the blank group. By the fourth grouting, the curdlan was close to saturation, so it no longer absorbed more liquid. As the grouting progressed, the higher the concentration of curdlan sand sample, the less cement was retained. This is because the pores inside the sand sample have been filled with curdlan and the generated calcium carbonate, and the excess cement gradually gathered at the top of the sand sample and reacted with the bacterial solution to form a "calcium carbonate layer" on the top. By the last grouting, the retention rate of the cement was about 20%. The increase of curdlan content can effectively increase the retention amount of cementing fluid and improve the utilization rate of cementing fluid.
[0035] Example 4 Effect of adding curdlan during grouting on microbial adsorption rate After the binder solution has been allowed to stand, inject the prepared bacterial solution and place it in a 30°C constant temperature incubator for 20 hours.
[0036] Then open the grouting port, collect the overflowing bacterial liquid, use a spectrophotometer to measure the absorbance of the collected liquid at 600nm, and subtract the measured value from 1 to roughly calculate the microbial adsorption rate.
[0037] Figure 3 The results show that during the 14 rounds of grouting, the microbial adsorption rate of the 0.5% mass concentration of curdlan and the blank group was significantly higher than that of other groups, and more microorganisms could be adsorbed. The water holding rate of curdlan with a mass concentration of less than 0.5% was lower, thus reducing the attachment of microorganisms.
[0038] Example 5 Effect of the addition of curdlan on the unconfined pressure of sand column After 14 rounds of grouting, the sand column was demoulded, the specimen was gently rinsed with deionized water, and placed in a 55 °C oven to constant weight.
[0039] Grind the upper and lower surfaces of the sand column flat, place it on the workbench of the unconfined pressure gauge, turn on the machine and record the pressure readings. Stop pressurizing when the pressure value drops sharply and record its peak pressure.
[0040] Figure 4 This is the result diagram of calcium carbonate generation in different parts of the sand column; Figure 5 The test results of the unconfined compressive capacity of the Curran mortar column with different mass concentrations; The results showed that the maximum pressure of the 0.5% mass concentration of curdlan group could reach 225KPa, which was about 1.7 times that of the blank group.
[0041] Example 6 Effect of the addition of curdlan on the amount of calcium carbonate produced Collect the sand column that has passed the UCS test, divide it into two parts as evenly as possible, put it in a beaker and weigh it as mL, add excess 1 moL / L hydrochloric acid, react to constant weight, and record the weight at this time as m2. The weight of calcium carbonate can be calculated using m=m1-m2.
[0042] The results show that although the quality of calcium carbonate at the top of the curdlan group is very high, its unconfined compressive strength still depends on the weak part of the sand column. Therefore, when the quality of calcium carbonate generated is similar, the more uniform the distribution of calcium carbonate, the better the integrity of the sand sample, and the greater its unconfined compressive strength. The calcium carbonate content of the upper part of the 0.5% curdlan group reached 12.26%, and the calcium carbonate content of the lower part reached 9.23%. The total amount of calcium carbonate generated in the upper and lower parts exceeded that of the blank group, and the difference between the upper and lower parts was small, only about 3%. Compared with other groups, the unconfined compressive strength of the 0.5% curdlan group was the largest, reaching an average of 255KPa, which is 1.75 times that of the blank group. Due to its superior water retention performance, high-concentration curdlan can absorb a large amount of cementing liquid and bacterial liquid, and react in the sand sample to generate a large amount of calcium carbonate, which makes the sand sample solidify well. However, low concentration of curdlan plays a greater role due to its colloidal properties. It cannot absorb a large amount of cementing liquid and bacterial liquid. On the contrary, the colloid will cause blockage of the channel and fill the original pores between the sand particles. After drying, the water in this small amount of curdlan evaporates, forming voids inside the sand sample. Therefore, the unconfined compressive strength is smaller than that of the blank group.
[0043] Example 7 Microscopic Characterization of Sand Column with 0.5% Mass Concentration Curdlan Take a small amount of sand from the center of the blank sand column in Example 5, spray gold for 90 seconds, and observe the mineral morphology with a scanning electron microscope (SEM). Take an appropriate amount of powder for X-ray diffraction spectrum (XRD) analysis. Take an appropriate amount of particles and grind them with potassium bromide into a cake for Fourier infrared (FTIR) analysis.
[0044] Take a small amount of sand from the center of the 0.5% mass concentration of curd group sand column in Example 5, spray gold for 90 seconds, and observe the mineral morphology with a scanning electron microscope (SEM). Take an appropriate amount of powder for X-ray diffraction spectrum (XRD) analysis.
[0045] Figure 6 This is the XRD diagram of the sand column particles of the curdlan group with a mass concentration of 0.5%. Through the main diffraction peaks of XRD and the retrieval of the standard PDF card, it was found that the mineral components of the sand column are silicon dioxide and calcium carbonate. The crystal form of calcium carbonate was calcite after comparison.
[0046] Figure 7 This is the FTIR spectrum of the sand column particles with a mass concentration of 0.5%. −1 There is a broad and intense hydroxyl stretching band at 2927 cm −1 and 1412 cm −1 The weak CH stretching vibration and symmetric deformation vibration at 724 cm −1 CO in-plane deformation appears around 876 cm −1 CO3 appears around 2- The out-of-plane deformation vibration peak is at 1432 cm −1 CO stretching vibration appears around 1756 cm −1 The characteristic peaks of CaCO3 due to CO stretching vibration appear on the left and right.
[0047] Figure 8 and Fig. 9 The SEM images of the sand column with 0.5% mass concentration of curdlan and the sand column with blank group are shown. It can be seen that the morphology of the sand column in the blank group is long prism. The calcium carbonate crystals produced in the sand column environment with curdlan are stacked rhombuses. Each rhombus particle is composed of a combination of multiple 2-4 micron hexahedral rhombuses, which are inlaid and closely connected. The surface of the hexahedral rhombus is smooth and the edges are clear. Among them, the large-sized amorphous irregular mass-like substances are dissolved curdlan, and a small amount of calcium carbonate particles are distributed in the dissolved curdlan. Most of the particles grow on the surface of the sand particles to form flower clusters of calcite aggregates. The formation of flower clusters of calcite aggregates may be because the intermolecular microspaces formed by the mutual aggregation of water-soluble organic matter during the MICP mineralization process are adsorbed on the specific crystal faces of the crystals, becoming the restricted space for crystal growth, resulting in the formation of spherical calcite crystals. Therefore, the formation of spherical calcite is due to the coverage of curdlan on the sand particles, which causes the crystal morphology to change. At the same time, flower-like calcite aggregates can be clearly observed in the SEM images of the column with curdlan added, and previous researchers observed a large number of flower-like hexahedral calcium carbonate aggregates when studying the effect of anionic polymers (polyglutamic acid) on MICP cementation. Therefore, the above calcium carbonate aggregates are induced by curdlan, and this type of morphology is densely arranged and better connects the loose sand particles.
[0048] In addition, it was found that there were bacterial holes with a diameter of about 1 μm left on the surface of a small amount of calcium carbonate aggregates, which were left by the death of bacteria. This shows that in the curdlan enhanced MICP solidification sand experiment, bacteria mainly acted as nucleation sites for calcite precipitation.
[0049] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
[0050] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention, but the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for consolidating sandy soil by using curdlan combined with MICP technology, characterized in that: The specific steps include: Step 1: Weigh the sieved standard sand, mix it with the corresponding mass concentration of curdlan, and put it into a customized mold to make a sand column sample with a height of 70-90mm; Step 2: After adding the filtered and sterilized urea solution to the sterilized culture medium, the bacteria are inoculated into the culture medium and cultured with shaking to obtain a Bacillus pasteurianus bacterial solution in the logarithmic growth phase; Step 3: Mix equal volumes of calcium chloride solution and urea solution to prepare a cementing solution; Step 4: Inject 1.1 times the pore volume of sterile water through the grouting port of the mold and place it in an incubator to saturate the sample; Step 5: After saturation, inject the fixative solution and let it stand in the incubator; Step 6: After standing still, inject the cementing liquid and stand still in the incubator; Step 7: centrifuge the bacterial solution in step 2, discard the supernatant and use fresh culture medium to make a bacterial solution resuspension with an OD of 1, inject it into the incubator and let it stand after the step 6 is completed, wherein step 6 and step 7 constitute one round of grouting, and a total of fourteen rounds of grouting are performed. After the last round of injection of the binder and bacterial solution resuspension, react for 20 hours; Step 8: After grouting, demould the sand column, rinse the specimen with deionized water, put it into an oven and dry it to constant weight for unconfined compressive strength (UCS) test.
2. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 1, the weight of the standard sand is 130-150g, and the fine sand is sieved through a 55-65 mesh sieve. The customized mold is a PVC cylinder with an open top and a sealed bottom. The inner diameter of the PVC cylinder is 35-38mm and the height is 110-130mm. A 200μL pipette tip is inserted into the bottom as a sample addition channel, and two layers of medical gauze are placed on the bottom of the mold.
3. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 2, the culture medium needs to be sterilized at high temperature and high pressure before adding the filtered and sterilized urea solution. The culture medium is NB-Urea liquid culture medium, and the components of NB-Urea liquid culture medium include at least 8-12 g / L of peptone, 4-6 g / L of beef extract, 4-6 g / L of sodium chloride, and 8-12 g / L of ammonium sulfate. After the bacteria are inoculated into the culture medium, they are shaken and cultured for 12-15 hours, the culture temperature is 28-35°C, and the shaking speed is 170-190 rpm.
4. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 3, the concentration of the calcium chloride solution is 2 mol / L, the concentration of the urea solution is 2 mol / L, the concentration of the binder is 1 mol / L, and the binder is a volumetric mixture of the calcium chloride dihydrate solution and the urea solution.
5. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 4, after sterile water was injected into the customized mold, it was placed in a constant temperature incubator at 30°C for 24 h to saturate the sample, and the injection rate of the peristaltic pump was 1 mL / min.
6. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 5, after injecting the fixative solution, the mixture is placed in a 30° C. constant temperature incubator for 6 hours. The fixative solution is 0.05 mol / L calcium chloride dihydrate solution.
7. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 6, after injecting the binder solution, the mixture is placed in a constant temperature incubator at 30°C for 6 hours.
8. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 7, the Bacillus pasteurianus bacterial solution is centrifuged at 4°C and 6000r for 5 minutes, and the bacterial solution resuspension is injected and then placed in a constant temperature incubator at 30°C for 20 hours.
9. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: In step 8, the unconfined compressive strength (UCS) test is carried out using a YYW-Ⅲ digital lime unconfined pressure gauge.
10. The method for consolidating sandy soil by using curdlan combined with MICP technology according to claim 1, characterized in that: The liquid injection amount in step 4, step 5, step 6 and step 7 is 1.1 times the pore volume of the sand sample.
Citation Information
Patent Citations
Method for reducing pouring times of MICP solidified soil
CN115354644A
Method for synergistically solidifying sandy soil through MICP-modified silk fibroin
CN115895666A
Cited By
Sand solidification agent based on gamma-polyglutamic acid and microbial mineralization and application method thereof
CN121538106A
